An academic kickstart: How librarian involvement enhances students’ academic literacy - Thorn, Jessica (Septentrio Conference Series, 2021)
In 2017 only 30 students out of 120 inthe nursing education program passed the examination assignment, a scientific report,on their first course. The coordinators of the course set out together withtheir liaison librarian to change the depressing scores. They developed change in the course content and assignments were made to strengthen the students’ academic literacy. The teachers offered lectures about the nursing profession,science and nursing theory, the research process, ethics, communication and scientific writing. The liaison librarian developed a set of five lectures, workshops and a reference quiz. The content of the five lectures is: •Brief library introduction •Reference management in Active Learning Classrooms •How to search for references and how to review scientific articles,lecture and workshop •How to search for scientific articles in Cinahl, lecture and workshop •An openfive-hour workshop together with librarians, Supplemental Instruction leaders1 and writing instructors from the Language Resource Center. Instead of diminishing the academic literacy demands,the course content has been increased with extended academic literacy training and the students’ tasks rely more than ever on scientific grounds. The changes were made to give all the students prerequisites to successfully pass the course carrying more knowledge with higher academic literacy and thus being better equipped for the rest of their education.This semester 90 of 120 students passed the scientific report examination on their first attempt. This session, An Academic Kickstart, will explain how the developmental change evolved and how the principles of andragogy and the implicit effort to locate the students’ point of departure have enhanced the students’ learning process and academic literacy. 1A Supplemental Instructor is a student who already has passed the course and help other students to understand the concepts of the course content and to find effective study strategies https://www.hv.se/en/student/jobb-och-karriar/si-leader